(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: The liver is the organ most subjected to the development of abscesses and made up 48 % of all visceral abscesses’ and 7% of all intra abdominal abscesses. Liver abscess should be suspected when there is a combination of fever, leucocytosis, constitutional symptoms, and pain in the right upper quadrant, and tenderness over the liver or right lower rib cage. The liver is affected by a number of local and disseminated infections; their frequency and types vary considerably around the world. Parasitic disorders are more prevalent in developing countries. Methods: It was a cross-sectional descriptive study. The cases were taken from the admitted patients of Medicine unit of SMCH, Chittagong. The study was conducted over a period of one year with a sample size of 50 patients and sample was taken by purposive sampling. Results: Among 50 patients 40 (80%) were diagnosed as ALA and 10 (20%) were diagnosed as PLA. ALA cases are common in 21-30 years age group & PLA cases are more common in >50 years of age group. Majority of the cases were from rural area. Common clinical features were fever, abdominal pain, nausea and tender hepatomegaly. Diarrhea was present on admission in 7 (15.9%) patients of ALA. Anaemia was common in both but polymorphonuclear leucocytosis was moderate to severe in PLA. Microscopic examination of stool samples for E. Histolytica trophozoites was positive in 3 (7.5%) cases and cysts in 4(10%) cases. Nine patients had right sided pleural effusion. Conclusions: Clinical features are common in both ALA and PLA. Liver abscesses are more common in men and more prevalent in rural areas. ALA more commonly occurs in 21-30 years age group but can occur at any age. Pyogenic abscess is more common in older age group (>50 years) and E. Coli is the commonest organism. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 44-48